Intercontinental comparison of fish ecomorphology: null model tests of community assembly at the patch scale in rivers. Issue 1 (1st February 2014) - Montaña, Carmen G.; Winemiller, Kirk O.; Sutton, Andrew
Abstract : Community assembly is affected by environmental filtering that restricts viable phenotypes and by species interactions that impose limits on interspecific trait similarity. Relative influences of these processes should vary according to habitat features and dispersal. Species dispersion within assemblage trait space also should vary in relation to species richness, strength of competition, and the spatiotemporal scale of analysis. We examined ecomorphological diversity of two freshwater fish families (Neotropical Cichlidae, Nearctic Centrarchidae) to test theories of local assembly from regional species pools and theories of species packing within mesohabitat patches. Cichlid and centrarchid assemblages were surveyed in four floodplain rivers (two in South America and two in North America) during low‐water periods when fish densities are highest. Surveys were conducted in four mesohabitat types (submerged wood, leaf litter, rocks, sand bank) within river channels and floodplain lakes. We measured 23 morphological traits associated with locomotion and feeding. Principal components analysis was performed on the species × traits matrix, and species axis scores were used to calculate species pairwise Euclidean distances and indices of dispersion within assemblage morphospace: mean nearest‐neighbor distance (indicating similarity), mean distance to centroid (assemblage morphospace size), and standard deviation of nearest‐neighbor distance (evenness of dispersion within assemblage morphospace). A null model was used to assess whether patterns were significantly nonrandom. When data for all mesohabitat types were combined for each river, species were significantly overdispersed and the assemblage morphospace was larger than predicted at random in every case. Analysis of assemblages within mesohabitat patches of different types revealed, in every case, significant overdispersion of species in morphospace indicative of limiting similarity. The total assemblage morphospace was greater than expected for tropical cichlids, but not for temperate centrarchids. Trends of species dispersion with assemblage morphospace in relation to species richness within mesohabitat patches were not consistent among or within river systems, possibly indicating that patches were already saturated with these perciform fishes. Interregional comparisons suggest an influence from both adaptive diversification and environmental filtering at broad spatial scales. At the scale of mesohabitat patches in lowland rivers, cichlid and centrarchid assemblages revealed patterns of trait complementarity that imply limiting similarity and strong influence of biotic interactions.